Bright blue emissions on UV-excitation of LaBO3 (B=In, Ga, Al) perovskite structured phosphors for commercial solid-state lighting applications - B. V. Naveen Kumar; T. Samuel; Samatha Bevara; K. Ramachandra Rao; Satya Kamal Chirauri (Chimica Techno Acta)
Bright blue photoluminescence (PL) was obtained from Bi3+-activated LaBO3 (B = In, Ga, Al) perovskite nanophosphors. A cost-effective and low-temperature chemical route was employed for preparing Bi3+ doped LaBO3 (B=In, Ga, Al) which were then annealed at 1000 °C. The phase formation, morphological studies and luminescent properties of the as-prepared samples were performed by X-ray diffraction (XRD), scanning electron microscopy (SEM), photoluminescence and optical absorption spectroscopy. Comparison of emission intensities, lifetime studies, energy band gaps and color purity of all samples (pure and Bi3+ doped) were investigated for promising applications in UV light-emitting diodes, variable frequency drive (VFD), field emission display (FED), and other photoelectric fields.